Ebelerde Örgütlenme ve İş Doyumunun Belirlenmesi - (:unkn) unknown (My University, 2017)
Amaç: Araştırma, iki doğum hastanesinde görev yapan ebelerin örgütlenme ve iş doyumlarını belirlemektir. Gereç ve Yöntem: Araştırma İstanbul'da devlete bağlı iki kadın doğum hastanesinde 25 Ocak-25 Mart 2014 tarihleri arasında yapıldı. Araştırmanın evrenini iki kadın doğum hastanesinde çalışan tüm ebeler, örneklemeni ise araştırmaya katılmayı kabul eden toplam 82 ebe oluşturdu. Araştırma verilerinin toplanmasında iki bölümden oluşan "Bilgi Formu" kullanıldı. Formun ilk bölümü ebelerin demografik ve bireysel özellikleri; ikinci bölümünde ise, mesleki bilinç ve örgütlenme konusundaki görüşlerini içeren sorulardan oluştu. Ayrıca ebelerin iş doyumlarını belirlemek için "Minnesota İş doyum Ölçeği" kullanıldı. Bulgular: Araştırmamıza katılan ebelerin %56,1'i lisans mezunu, %54,9'unun mesleği isteyerek seçtiği ve %70,7'sinin becerisine uygun klinikte çalıştığı belirlendi. Ebelerin %61'inin ulusal-uluslararası düzeydeki sağlık örgütlerini bildiği, %30,5'inin meslekle ilgili derneklere üye, %26,8'inin Türk Ebeler Derneğine üye olduğu saptandı. Araştırmaya katılan ebelerin iş doyumu ölçek puanı ile meslekten ayrılmayı düşünme ve yöneticilerin tutumunun iş doyumunu etkilediğini düşünme durumu arasındaki farkın anlamlı olduğu belirlendi (p<0,05). Eğitim düzeyinin, mesleği isteyerek seçme, hizmet süresi ve çalıştığı kliniğin iş doyumunu etkilemediği saptandı (p>0,05). Sonuç: Araştırmaya katılan ebelerin %61'inin ulusal ve uluslararası düzeydeki sağlık örgütlerini bildiği, %30,5'inin meslekle ilgili derneklere üye, %26,8'inin Türk Ebeler Derneği'ne üye olduğu saptanmıştır. Türk Ebeler Derneği'ne Bireysel özelliklerin, performans değerlendirmesi ve yönetici tutumunun ebelerin iş doyumunu etkilediği belirlenmiştir.

Objective: The purpose of the study is to determine the union and the job satisfaction of midwives working in two maternity hospitals. Materials and Methods: The research was conducted the dates between 25/1/2014 and 25/3/2014 in two maternity hospitals in Istanbul. All midwives working in two of the hospitals in Istanbul formed the population for the research and the total of 82 midwives participated in the study for sampling. The collection of data is derived from the information form which consisting two parts. The first part of the form including demographic and personal characteristics of the midwives, and the second part is including questions regarding their views on the professional awareness and the organization. Also to determine the job satisfaction of midwives, "Minnesota Satisfaction Questionnaire" was used. Results: 56.1% of bachelor's degree graduates of the midwives who participated in our research, 54.9% of them have chosen the profession willingly and 70.7% of them working in clinics that are matched with their skill set. 61% of midwives know the health organizations on the national and the international stage, 30.5% of them are the members of various professional associations and 26,8% of them are found to be members of the Turkish Midwives Association. The midwives participated in the study shows that there is a significant meaning between the job satisfaction scores and the scores of the consideration of leaving the job due to effect on job satisfaction caused by managers' attitude (p<0,05). It is found that, the level of education, the consciousness on job selection, the period of service, and the work place do not have an impact on job satisfaction. (p> 0.05). Conclusion: It was determined that 61% of the midwives participating in the survey were known of national and international health organizations, 30.5% were members of associations related to the profession and 26.8% were members of the Turkish Midwives Association. The individual properties are determined by performance evaluation and manager's attitude affect the job satisfaction of midwives.
The Organization in Midwives and Determination of Job Satisfaction
Keywords: Kadın Hastalıkları ve Doğum; Aile Çalışmaları; Sağlık Politikaları ve Hizmetleri; Hemşirelik; Psikoloji; Kadın Araştırmaları